The role of the multi-drug resistance 1, p53, b cell lymphoma 2, and bcl 2-associated X genes in the biologic behavior and chemotherapeutic resistance of canine transmissible venereal tumors - Alzate, Juliana M.; Montoya-Florez, Luis M.; Pérez, Jorge E.; Rocha, Noeme S. [UNESP]; Pedraza-Ordonez, Francisco J. (Wiley, 2019)
Background: Canine transmissible venereal tumors (CTVTs) generally have different cytomorphologic subtypes and phases of progression. Some tumors have variable biologic behavior including a progressive increase in tumor aggressiveness and variable responses to chemotherapy. This behavior is partially due to high p-glycoprotein expression by tumor cells, which leads to the expulsion of chemotherapeutic drugs. Other possible causes include changes in pro- and anti-apoptotic genes from the BCL-2 family and DNA repair systems, which are associated with the p53 gene family. Objectives: We aimed to determine the relative expression of the multi-drug resistance 1 (MDR1), p53, b-cell lymphoma 2 (BCL2), and bcl 2-associated X (BAX) genes in CTVT before and after therapy and establish a relationship with treatment responses, cytomorphologic patterns, and tumor progression identified with histopathology. Methods: RT-qPCR was performed on 21 CTVT tumor samples before and after initiating chemotherapy to determine specific gene expression. Normal canine testicular tissue was used as a negative control for all experiments. Results: MDR1 expression was decreased before and after initiating vincristine therapy in CTVT tumor tissues compared with normal canine testicular tissue; p53 and BAX were overexpressed at both time points compared with normal tissue, and no statistical differences were seen between the different morphologic types. However, BAX expression was decreased in the group with quick therapeutic responses but was still overexpressed compared with normal testicular tissue. In the group with the slowest chemotherapeutic responses, BCL2 was overexpressed. Conclusion: The findings of this study showed a relative increase in MDR1 gene expression in response to chemotherapy and higher expression in plasmacytoid CTVTs compared with the other cytomorphologic patterns. BCL2 overexpression was related to a favorable prognosis, and p53, BAX, and BCL2 were expressed independent of the cytomorphologic CTVT type. All of the genes were expressed independent of tumor progression, as noted on histopathology.
Keywords: apoptotic proteins; BAX; BCL-2; CTVT chemotherapy; MDR-1